2023
DOI: 10.1109/tvt.2022.3212025
|View full text |Cite
|
Sign up to set email alerts
|

LDPC Coded Compressive Sensing for Joint Source-Channel Coding in Wireless Sensor Networks

Abstract: The novel concept of joint Compressive Sensing (CS) and Low Density Parity Check (LDPC) coding is conceived for Joint Source-Channel Coding (JSCC) in Wireless Sensor Networks (WSNs) supporting a massive number of signals. More explicitly, we demonstrate this concept for a specific scheme, which supports a massive number of signals simultaneously, using a small number of Internet of Things Nodes (IoTNs) based on the concept of CS. The compressed signals are LDPC coded in order to protect them from poor transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Explicitly, Figure 9 is produced by generating ba artificially and then measure the MI of be . The details of generating the LDPC decoder's EXIT function are similar to the processing introduced in [32], [33]. Figure 9 shows that upon increasing the number of LDPC inner iterations I LDPC , the LDPC EXIT function moves downwards, which results in improved decoding performance.…”
Section: Simulation Resultsmentioning
confidence: 98%
“…Explicitly, Figure 9 is produced by generating ba artificially and then measure the MI of be . The details of generating the LDPC decoder's EXIT function are similar to the processing introduced in [32], [33]. Figure 9 shows that upon increasing the number of LDPC inner iterations I LDPC , the LDPC EXIT function moves downwards, which results in improved decoding performance.…”
Section: Simulation Resultsmentioning
confidence: 98%
“…In this case, opted for hiring 3 hidden layers and each layer has 6 neural nodes in the trained DNN. It has been shown that the DL module employed is easy to train at a low complexity and it has advantages compared to other signal processing algorithms available for correcting inconsistent LLRs such as lookup tables, which have a higher memory requirement [21].…”
Section: Mmse-ircmentioning
confidence: 99%
“…Since the MMSE-IRC detector rejects interference, there is no need for the NL-SOCA to consider interference during the detection process. Furthermore, a DL-aided LLR correction technique [21] is conceived for further improving the performance.…”
Section: Introductionmentioning
confidence: 99%